Satisfactory postoperative alignment following retrograde SIGN Fin nailing for femoral shaft fractures: A case–control study - Wilson, Nathaniel M. (OTA Int, 2019)
PURPOSE: In developing countries, long bone fractures following trauma are a significant contributor to morbidity, and operating room resources are often limited in these settings. The Surgical Implant Generation Network (SIGN) Fin nail may reduce the challenges of retrograde intramedullary nailing of femoral fractures without fluoroscopy. In contrast to the traditional SIGN nail placed in a retrograde fashion, the Fin nail does not require proximal interlocking screws. Instead, the nail achieves stability through an interference fit within the proximal femoral canal. The purpose of this study is to compare postoperative alignment in femoral shaft fractures treated with either a retrograde SIGN Fin nail or a standard retrograde SIGN nail. METHOD: Using the SIGN online surgical database, we identified all femoral shaft fractures treated with a retrograde SIGN Fin nail at 2 African hospitals. Two examiners independently classified fracture patterns using the Arbeitsgemeinschaft für Osteosynthesefragen/Orthopaedic Trauma Association (AO/OTA) classification system. Using an on-screen protractor tool, postoperative coronal and sagittal plane alignment were measured and recorded as deviation from anatomic alignment (DFAA), with units in degrees. Available patient demographics and surgical details were also recorded. Fin nail cases were matched in a 1:1 ratio to retrograde standard SIGN nail cases based on AO/OTA fracture type. RESULTS: Twenty-eight retrograde Fin nail cases were identified, and 28 matched retrograde SIGN nail cases were selected. The Fin nail and retrograde SIGN nail groups were well matched in terms of demographics, AO/OTA fracture type, and surgical characteristics. There was no significant difference in postoperative coronal or sagittal plane alignment between the groups. There were no cases in either group of average postoperative malalignment >5° in any plane. CONCLUSION: The SIGN Fin nail appears to achieve satisfactory radiographic alignment without the need for proximal interlocking screws, making it an attractive implant for retrograde femoral shaft fracture fixation in resource-limited settings. Further research is required to validate these findings and determine long-term Fin nail clinical outcomes.